Morphological and Anatomical Characteristics of Cocoa Plants That Grow at Different Heights - Bisma Wahyu Farhanandi; Indah, Novita Kartika (LenteraBio : Berkala Ilmiah Biologi, 2022)
Cocoa (Theobroma cacao L.) or known as chocolate is one of Indonesia’s leading commodities with high diversity. To increase the productivity of cocoa, superior cultivars are needed that are suitable for their environment so that a study of morphological and anatomical characters is needed. The purpose of this study was to determine the superior cultivars in terms of morphological, ecological, and anatomical characters and to know the relationship between the morphological and anatomical characteristics of Cocoa plants that grow at different heights. This exploratory descriptive research was conducted in Madiun and Blitar. Samples were taken by purposive sampling as many as 18 individual plants in three cocoa cultivars in Madiun and Blitar. The morphological characters were 120 morphological characters and analyzed by Principal Component Analysis to determine the marker characters. The ecological characters used were altitude, temperature, humidity, and pH and anatomical characters were observed using whole mount leaf preparations in order to calculate the density and stomatal index. The results showed that the altitude caused differences in morphology and anatomy of the cocoa leaves, while the quality of the beans was caused by the shading factor. Differences in altitude have an impact on morphological characters that vary, especially on the characters of leaves, flowers, fruits, and seeds, while leaf anatomy differs in stomatal density and stomata index. Shaded cocoa plants will have a higher stomata index and produce more and quality beans.